Comparison Between GVM and Wavelet GVM Model to Forecast Monthly Electricity Demand of Erbil Governorate - Aziz, Azhy A.; Hasan , Kovan O. (Mitanni Journal of Humanitarian Sciences, 2023)
Collecting and getting electricity demand is one of the most important projects at any place and community collecting information about its consumption. As a result of not having a good strategy for generating and its consumption might be useless economically. There should be a good plan to develop generating electricity projects to decrease the load problem. The main purpose of this study is to estimate the Grey Verhulst model to realize the average demand for electricity per month. And knowing the rate of electricity consumption and appropriate treatments for this problem. All of the time typical technical series models are used for data to achieve and collect the results. There is a set of theories that can be performed for analysis in this case, grey system theory is one of those theories which is including a set of models like GM (1, 1), GVM, FGM and FRGM to allow expectations for some information in the future based on a set of original data that is going to be less and uncertain data. Forecasting is a branch of statistics that deals with parameters and (OLS) are one of the methods of guessing parameters in mathematical examples, this study implemented Grey Verhulst Model on the amount of demand for electricity for twelve months (Mar-2016 to Feb-2017).